ANALISIS PENANGANAN DETENI SAAT PANDEMI DI RUANG DETENSI IMIGRASI (STUDI KASUS KANTOR IMIGRASI KELAS I KHUSUS NON TPI JAKARTA SELATAN) - Idham, Riyadi; Wiraputra, Anindito Rizki (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In preventing the Covid-19 pandemic, immigration has a security function which is carried out by selecting the intentions and objectives of foreign nationals to Indonesian territory by examining visa applications, including in handling detainees in the detention room. The problem in this study is whether the arrangements for handling detainees in the detention room of the Class 1 Immigration Office for Non TPI, South Jakarta can be implemented during the covid-19 pandemic. How to optimize the handling of detainees during the covid-19 pandemic in the detention room of the Class 1 Immigration Office for Non TPI, South Jakarta. This research method is empirical normative using primary data and secondary data. The results of the study stated that the arrangements for handling detainees in the detention room of the Class 1 Immigration Office for Non TPI, South Jakarta, could not be fully implemented during the Covid-19 pandemic. This is because until now there is no regulation specifically for the Class I Immigration Office for Non TPI related to the handling of detainees in the detention room, thus causing the absence of standard operating procedures for officers. Optimization of the handling of detainees during a pandemic in the detention room of the Class 1 Immigration Office for Non TPI Special South Jakarta is through the issuance of the Regulation of the Director General of Immigration regarding the handling of detainees during a pandemic in the detention room at the Immigration Office Class 1 Special for Non TPI South Jakarta.